PENGGUNAAN MEDIA AUDIO PADA PELAJARAN BAHASA INGGRIS DALAM MENYAMPAIKAN ISI LAPORAN UNTUK MENINGKATKAN PRESTASI BELAJAR : (The Use Of Audio Media In English Learning To Deliver Report Contents To Improve Learning Achievement) - Yusuf, Nuraeni (Uniqbu Journal of Social Sciences, 2020)
One of the learning environments that involve students actively in learning can be achieved by using audio media. The subjects of this study were class IX 3 UPT SMP Negeri 1 Tellu Limpoe, Sidenreng Rappang Regency in the 2018/2019 academic year, totaling 33 students. The choice of research subjects was because students were less able to socialize and conclude the reports they heard so that audio media were used to overcome them. The research procedure consisted of four stages in each cycle, namely planning, acting, observing, and reflecting. The results showed that the use of audio media in English lessons in the material concluded that the contents of the report had a major contribution in the effort to improve student achievement, marked by an increase in student formative values. In the first cycle, the students' learning completeness reached 70% and in the second cycle, it reached 100%.